HUBUNGAN LINGKAR PINGGANG DAN INDEKS MASSA TUBUH DENGAN DERAJAT NYERI PENDERITA LOW BACK PAIN BERDASARKAN VISUAL ANALOG SCALE PADA LANSIA DI PUSKESMAS HELVETIA - Marpaung, Alexander Parlindungan; Gurning, Claudio Immanuel; Siagian, Laura Octavina (Universitas Methodist Indonesia, 2023)
Low back pain (LBP) or low back pain (NPB) is pain in the lower back. Pain sensation inthe anatomy of this area is influenced by different variations of pain duration. This pain can be local, peripheral, or both.The aim of this study was to determine the relationship between waist circumference and body mass index with the degree of low back pain in theelderly. The type of research used is observational analytic measurement research, with across-sectional design. The results of the study found a significant relationship between waist circumference and body mass index on the degree of pain in elderly low back pain patients at the Helvetia Health Center.